Use of Trichoderma spp. in biodegradation of Carbendazim - SHARMA, PRATIBHA; SHARMA, MANIKA; RAJA, M; SINGH, D V; SRIVASTAVA, MUKESH (The Indian Journal of Agricultural Sciences, 2016)
Trichoderma spp. are most popular biocontrol agents (BCA) known worldwide for their great ability to combat different soil and foliar diseases of agricultural crops. The use of biocontrol agents in IPM strategies requires the effective strains compatible with pesticides which can be well utilized in an integrated pest management system and also suitable to reduce the residual effect of pesticides. Keeping this in view, the study was designed to evaluate to lerance levels and biodegradation of benzimidazole fungicide (Carbendazim) by Trichoderma harzianum, Trichoderma viride and Trichoderma atroviride at three concentrations 100, 150 and 200 ppm were determined. The maximum per cent inhibition of T.harzianum, T.viride and T.atroviride in carbendazim amended media were 60, 83 and 93 at with spore production of 2.0×106, 1.4×106 and 0.8×106spore/µl at 200 ppm. Biodegradation per cent of carbendazim after 5 days of incubation determined through HPLC analysis were 85% in T.harzianum, 47% in T.viride and 21% in T.atroviride, thus clearly indicating the biodegradation property of Trichoderma spp.